Functional analyses of the NRT2 family of nitrate transporters in Arabidopsis - Xu, Na; Cheng, Li; Kong, Yuan; Chen, Guiling; Zhao, Lufei; Liu, Fei (Frontiers in Plant Science, 2024)
Nitrogen is an essential macronutrient for plant growth and development. Nitrate is the major form of nitrogen acquired by most crops and also serves as a vital signaling molecule. Nitrate is absorbed from the soil into root cells usually by the low-affinity NRT1 NO3 -transporters and high-affinity NRT2 NO3 -transporters, with NRT2s serving to absorb NO3 -under NO3 --limiting conditions. Seven NRT2 members have been identified in Arabidopsis, and they have been shown to be involved in various biological processes. In this review, we summarize the spatiotemporal expression patterns, localization, and biotic and abiotic responses of these transporters with a focus on recent advances in the current understanding of the functions of the seven AtNRT2 genes. This review offers beneficial insight into the mechanisms by which plants adapt to changing environmental conditions and provides a theoretical basis for crop research in the near future.